Development of an Electronic Archive “Rehabilitation after Soft-Tissue Lesions of the Knee Complex” for the Post-Graduate Medical and Health Professions Education - R. Yoshinov, Radoslav; R. Yoshinov, Borislav; B. Koleva, Ivet (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2026)
The objectives of the current article include the preservation of the scientific heritage of Bulgarian Ortho-rehabilitation school through development of an electronic archive in the field of “Orthopedic Rehabilitation of soft-tissue lesions of the knee complex”, and analysis of the efficacy of its application in the post-graduate medical and healthcare education.